2016
DOI: 10.1891/0886-6708.vv-d-13-00196
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Bystander Behavior Intentions Toward Friends to Prevent Dating Violence: Development of the Bystander Behavior Intentions-Friends Scale Through Concept Mapping and Exploratory Factor Analysis

Abstract: Bystander behavior interventions aim to reduce violence by encouraging individuals to intervene in a safe and effective manner when they hear or see circumstances that could lead to violence. This study used a participatory-based approach to develop a 9-item scale to measure bystander behaviors to prevent dating violence among friends. Predominantly, female students (N = 37) on a college campus in the Mid-Atlantic region of the United States were asked to define bystander behaviors. Responses were thematically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…The authors used IBM to guide this evaluation and included items from each of the main theory domains. All measures were focused on behaviors toward friends, which students reported as being more important and feasible to perform (Borsky, McDonnell, Rimal, & Turner, 2016) and is also consistent with prior research (Kleinsasser, Jouriles, McDonald, & Rosenfield, 2015;Levine, Cassidy, Brazier, & Reicher, 2002). The behaviors focused on actions students can take to prevent victimization of dating violence.…”
Section: Methodsmentioning
confidence: 74%
See 1 more Smart Citation
“…The authors used IBM to guide this evaluation and included items from each of the main theory domains. All measures were focused on behaviors toward friends, which students reported as being more important and feasible to perform (Borsky, McDonnell, Rimal, & Turner, 2016) and is also consistent with prior research (Kleinsasser, Jouriles, McDonald, & Rosenfield, 2015;Levine, Cassidy, Brazier, & Reicher, 2002). The behaviors focused on actions students can take to prevent victimization of dating violence.…”
Section: Methodsmentioning
confidence: 74%
“…Bystander behaviors. This scale includes nine core behavioral actions (see the appendix), ranging from telling friends that they deserve to be treated well by their partners to letting friends know when one is concerned about them to taking action by removing friends from uncomfortable situations (Borsky et al, 2016). Respondents were asked to indicate if they had engaged in the actions within the last 3 months, with the option of responding "wasn't in the situation."…”
Section: Methodsmentioning
confidence: 99%
“…First, there was a decline in reported bystander behavior from baseline to follow-up in the two TakeCARE groups and the control group, but the decline in the TakeCARE groups was significantly smaller than the decline in the control group. Although other studies evaluating bystander behavior on college campuses over time have also reported declines (e.g., Gidycz, Orchowski, & Berkowitz, 2011; Jouriles, McDonald, et al, 2016, Study 1; Kleinsasser et al, 2014; Moynihan et al, 2015), some studies report increases in student bystander behavior after receiving bystander training (e.g., Borsky, McDonnell, Rimal, & Turner, 2016; Jouriles, McDonald, et al, 2016, Study 2; McMahon, Winter et al, 2015). Similarly, some studies report stability in levels of bystander behavior over time for students in control conditions who do not receive bystander training (e.g., Elias-Lambert & Black, 2016; Gidycz et al, 2011; Jouriles, McDonald, et al, 2016, Study 2).…”
Section: Discussionmentioning
confidence: 96%
“…(12,13). Bystanders are regularly considered to have a degree of detachment and objectivity in the situation, from which they are able to make rational decisions based on the particular circumstances, but it is important to note that Latane and Darley's original ideas, in the 1960s, about decision-making, highlighted that people's responses might have consequences for themselves, as well as for the victim (14).…”
mentioning
confidence: 99%